2010
DOI: 10.1186/1472-6963-10-240
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of mentoring functions on job satisfaction and organizational commitment of new staff nurses

Abstract: BackgroundAlthough previous studies proved that the implementation of mentoring program is beneficial for enhancing the nursing skills and attitudes, few researchers devoted to exploring the impact of mentoring functions on job satisfaction and organizational commitment of new nurses. In this research we aimed at examining the effects of mentoring functions on the job satisfaction and organizational commitment of new nurses in Taiwan's hospitals.MethodsWe employed self-administered questionnaires to collect re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 40 publications
4
75
0
1
Order By: Relevance
“…-Questionnaires were confirmed by 10 faculty members of the university. Reliability of organizational commitment questionnaire with Cronbach's alpha in Mosadeghrad & Ferdosi (4) study was 0.77 and in the current study was 0.84; job satisfaction with Cronbach's alpha in the study by Weng et al (15) was 0.86 and in the current study was 0.85. Lesage & Berjot (16) in an article entitled "validity of occupational stress assessment using a visual analogue scale" declared the reliability of VAS as a high level of correlation between the VAS and perceived stress scale (PSS) and in the current study it was 0.85 on parallel evaluation.…”
Section: Methodsmentioning
confidence: 77%
“…-Questionnaires were confirmed by 10 faculty members of the university. Reliability of organizational commitment questionnaire with Cronbach's alpha in Mosadeghrad & Ferdosi (4) study was 0.77 and in the current study was 0.84; job satisfaction with Cronbach's alpha in the study by Weng et al (15) was 0.86 and in the current study was 0.85. Lesage & Berjot (16) in an article entitled "validity of occupational stress assessment using a visual analogue scale" declared the reliability of VAS as a high level of correlation between the VAS and perceived stress scale (PSS) and in the current study it was 0.85 on parallel evaluation.…”
Section: Methodsmentioning
confidence: 77%
“…Research also has indicated that a relationship exists between job satisfaction and organizational commitment [38][39][40]. Organizational commitment involves individual employees' psychological attachment to the organization for which they work and therefore is a strong indicator of performance in the workplace [36].…”
Section: Variables Impacting Work-life Balancementioning
confidence: 99%
“…In addition, it influences the context as the structural capital that corresponds to the use of technology, information systems, internal communication and the standardized processes in the attention; As well as social capital integrated by social interaction, trust and shared vision. [6][7][8][9] In health institutions, organizational learning is the result of adequate knowledge management. It is a priority to show that staff apply, share and create knowledge in a collective and systematic way, providing a value for the organization, for people and for society.…”
Section: -5mentioning
confidence: 99%